2022
DOI: 10.1051/0004-6361/202142253
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of late-time X-ray flare and anomalous emission line enhancement after the nuclear optical outburst in a narrow-line Seyfert 1 Galaxy

Abstract: CSS J102913+404220 is an atypical narrow-line Seyfert 1 galaxy with an energetic optical outburst occurring co-spatially with its nucleus. We present a detailed analysis of multi-wavelength photometric and spectroscopic observations of this object covering a period of a decade since outburst. We detect mid-infrared (MIR) flares delayed by about two months relative to the optical outburst and with an extremely high peak luminosity of L4.6 μm > 1044 erg s−1. The MIR peak luminosity is at least an order of mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 114 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…Frederick et al (2021) reported TDE candidates in narrow-line Seyfert 1 galaxies. More recently, Zhang et al (2022) showed the TDE expected variability patterns in a narrow line Seyfert 1 galaxy. Meanwhile, Chan et al (2019Chan et al ( , 2020 modeled TDE variabilities in AGN with a preexisting accretion disk, and showed that about a 20 day long plateau could be expected around the central BH with masses of around 10 6−7 M e .…”
Section: Main Results and Necessary Discussionmentioning
confidence: 95%
“…Frederick et al (2021) reported TDE candidates in narrow-line Seyfert 1 galaxies. More recently, Zhang et al (2022) showed the TDE expected variability patterns in a narrow line Seyfert 1 galaxy. Meanwhile, Chan et al (2019Chan et al ( , 2020 modeled TDE variabilities in AGN with a preexisting accretion disk, and showed that about a 20 day long plateau could be expected around the central BH with masses of around 10 6−7 M e .…”
Section: Main Results and Necessary Discussionmentioning
confidence: 95%
“…However, this possibility seems unlikely based on the X-ray properties (Bykov et al 2024). In addition, the rapid (duration of <1 yr) optical flare can also rule out the normal AGN variability, as it is rarely seen in the light curves of AGNs (Drake et al 2011;Kankare et al 2017;Zhang et al 2022). The lack of detectable broad permitted lines prevents us from estimating the central BH mass of AT 2018cqh using the conventional linewidthluminosity-mass scaling relation.…”
Section: A Tde From a Candidate Imbh?mentioning
confidence: 99%
“…However, the situation is more complicated when the galaxy is an AGN, such that it is not immediately clear whether the change comes from an accretion disk (instability) or, less likely, from a (very rare) TDE or an SN IIn. The situation is also challenging when there is no pre-outburst spectrum available, or when there are only a few post-outburst spectra, so that long-lived AGN, rare TDE, or SN IIn scenarios cannot immediately be distinguished based on optical spectra alone (see the detailed discussion of Komossa et al [43] and Komossa et al [48]; and see Drake et al [49], Blanchard et al [50] and Zhang et al [51] for examples in NLS1-like galaxies).…”
Section: Namementioning
confidence: 99%